2022
DOI: 10.3390/pathogens11030331
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Orally Administered Nitrofurantoin against Animal African Trypanosomosis Caused by Trypanosoma congolense Infection

Abstract: Animal African trypanosomosis (AAT) leads to emaciation and low productivity in infected animals. Only six drugs are commercially available against AAT; they have severe side effects and face parasite resistance. Thus, the development of novel trypanocidal drugs is urgently needed. Nitrofurantoin, an antimicrobial, is used for treating bacterial urinary tract infections. Recently, we reported the trypanocidal effects of nitrofurantoin and its analogs in vitro. Furthermore, a nitrofurantoin analog, nifurtimox, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Previously, a 100% survival and cure were achieved with a dose of nitrofurantoin ≥30 mg/kg in T. congolense IL3000 infected mice, and therefore, this preliminary data served as a benchmark to compare the in vivo treatment efficacy of the structurally related compounds 4a , 7a , and 8b . Compared to nitrofurantoin, the test compounds 4a , 7a , and 8b showed increased in vitro trypanocidal activity against T. congolense IL3000 and decreased toxicity against MDBK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a 100% survival and cure were achieved with a dose of nitrofurantoin ≥30 mg/kg in T. congolense IL3000 infected mice, and therefore, this preliminary data served as a benchmark to compare the in vivo treatment efficacy of the structurally related compounds 4a , 7a , and 8b . Compared to nitrofurantoin, the test compounds 4a , 7a , and 8b showed increased in vitro trypanocidal activity against T. congolense IL3000 and decreased toxicity against MDBK cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown cross resistance with Trypan-blue only, which is not very closely related chemically, but formed the backbone through which suramin was developed (Wiedemar et al, 2018). Interestingly, trypan blue is virtually the definition of a substance that is not taken up by cells and has been used for decades in the 'trypan blue exclusion test' to distinguish live from dead cells (Strober, 2015), but is readily taken up by trypanosomes (De Koning, unpublished observation)presumably in the same way as suramin is.…”
Section: Multidrug Resistance and Cross-resistance Between Trypanocidesmentioning
confidence: 99%
“…The trypanocidal activity of azithromycin was demonstrated in vitro against T. congolense, T. b. brucei and T. evansi, and in vivo against T. congolense with no relapse for up to 90 days in infected mice with 100% survival rate ( Molefe et al, 2017 ). Another antibiotic, nitrofurantoin achieved complete cure at doses higher than 30 mg/kg when orally administered for 7 days in mice infected with T. congolense ( Suganuma et al, 2022 ). Terconazole, a synthetic triazole derivative used as antifungal agent, was found to exert promising activity against T. cruzi with IC 50 of 4.56 ± 0.32 μM in trypomastigotes and 5.96 ± 0.35 μM in amastigotes, which is more effective than the control drug benznidazole (IC 50 values of 12.71 ± 1.53 μM for trypomastigotes and 11.4 ± 0.5 μM for amastigotes) ( Reigada et al, 2019 ).…”
Section: Drug Repurposingmentioning
confidence: 99%